The Acentropinae (Lepidoptera: Pyraloidea: Crambidae) of Africa - Agassiz, David J. L. (Zootaxa, 2012)
The species of Acentropinae recorded from Africa are listed and described with illustrations of the adults and genitalia.Ten new synonymies are established. The following species are described new to science: Parapoynx zambiensis,Argyrophorodes angolensis, A. suttoni, Elophila acornutus, E. ealensis, E. minima, Nymphicula hexaxantha, Eoophylabelladotae, E. cameroonensis, E. carcassoni, E. citrialis, E. dentisigna, E. euprepialis, E. grandifuscalis, E. interopalis,E.kingstoni, E. piscatorum, E. platyxantha, E. principensis, E. ruwenzoriensis, E. stepheni, E. tanzanica. E. nyasalis kenyalis is described as a new subspecies.